Seroprevalence and associated risk factors of ovine neosporosis worldwide: a systematic review and meta-analysis - Romanelli, Paulo Roberto; Caldart, Eloiza Teles; Martins, Felippe Danyel Cardoso; Martins, Camila Marinelli; Matos, Andressa Maria Rorato Nascimento de; Pinto-Ferreira, Fernanda; Mareze, Marcelle; Mitsuka-Breganó, Regina; Freire, Roberta Lemos; Navarro, Italmar Teodorico (Semina: Ciências Agrárias, 2021)
Neosporosis, caused by the protozoan Neospora caninum, has been widely reported and discussed as a major disease associated with reproductive problems in herds of various animal species. This study aimed to perform a systematic review and meta-analysis on the prevalence and risk factors associated with ovine neosporosis worldwide. This is the first systematic review, which was performed according to the established preferred reporting items in systematic reviews and meta-analyses (PRISMA) guidelines to address ovine neosporosis. Four databases were used in this study: PubMed, SciELO, Web of Science, and Scopus. The selected keywords were "neospora AND sheep," "neosporosis AND sheep," "neospora AND lamb," "neosporosis AND lamb," "neospora AND ewe," and "neosporosis AND ewe." The meta-analysis calculations were performed with random-effects models for proportions, and heterogeneity was tested using the I2 test. This study identified 24 studies on ovine neosporosis, nine of which evaluated the factors associated with the risk of seropositivity. After meta-analysis, the pooled estimated prevalence was 12% (95% CI, 8-16%; IÂ² p-value < 0.01). The evaluation of the included studies allowed the identification of ovine neosporosis distribution in continents according to demonstrated prevalence rates. We confirmed via meta-analysis that the use of indirect immunofluorescence assay (IFAT) or enzyme-linked immunosorbent assay (ELISA) in the diagnosis of ovine neosporosis was not a source of data heterogeneity. The presence of dogs on the properties was reported as the main risk factor associated with the occurrence of ovine neosporosis; however, this was not confirmed by the meta-analysis.